A facile route for the preparation of silica foams using rice husk ash. Issue 3 (6th January 2019) - Hossain, SK Saddam; Mathur, Lakshya; Bhardwaj, Aman; Roy, Pradip Kumar
Abstract: This work aims to synthesize silica foam with around 75 vol. % open porosity without using any additive or pore forming agents, in order to prevent the generation of greenhouse gases during pore formation in the silica matrix. Waste rice husk ash (RHA) derived silica is used as a silica source, which is extracted through the alkali extraction synthesis route. Several physical characterizations such as X‐ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), differential thermal‐thermogravimetric (DTA‐TGA) and FTIR analysis have been done for RHA extracted silica. Silica foam specimens are fabricated through control compaction pressure and at low foaming temperature. Samples which are fired at 550°C for 30 minutes exhibit both a adequate apparent porosity (AP; 75.82%) and significant compressive strength ( 1.54 MPa). It can also be observed that the porosity and strength values are changed with the variation in compaction pressure and foaming temperature.